Surge dynamics and lake outbursts of Kyagar Glacier, Karakoram - V. Round (The Cryosphere, 2017)
The recent surge cycle of Kyagar Glacier, in the Chinese Karakoram, caused formation of an ice-dammed lake and subsequent glacial lake outburst floods (GLOFs) exceeding 40 million m3 in 2015 and 2016. GLOFs from Kyagar Glacier reached double this size in 2002 and earlier, but the role of glacier surging in GLOF formation was previously unrecognised. We present an integrative analysis of the glacier surge dynamics from 2011 to 2016, assessing surge mechanisms and evaluating the surge cycle impact on GLOFs. Over 80 glacier surface velocity fields were created from TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurement), Sentinel-1A, and Landsat satellite data. Changes in ice thickness distribution were revealed by a time series of TanDEM-X elevation models. The analysis shows that, during a quiescence phase lasting at least 14 years, ice mass built up in a reservoir area at the top of the glacier tongue, and the terminus thinned by up to 100 m, but in the 2 years preceding the surge onset this pattern reversed. The surge initiated with the onset of the 2014 melt season, and in the following 15 months velocity evolved in a manner consistent with a hydrologically controlled surge mechanism. Dramatic accelerations coincided with melt seasons, winter deceleration was accompanied by subglacial drainage, and rapid surge termination occurred following the 2015 GLOF. Rapid basal motion during the surge is seemingly controlled by high water pressure, caused by input of surface water into either an inefficient subglacial drainage system or unstable subglacial till. The potential lake volume increased to more than 70 million m3 by late 2016, as a result of over 60 m of thickening at the terminus. Lake formation and the evolution of the ice dam height should be carefully monitored through remote sensing to anticipate large GLOFs in the near future.